Analisis Yuridis Terhadap Penerapan Sanksi Pidana Tambahan Bagi Pemulihan Lingkungan Oleh Korporasi - Aullia Vivi Yulianingrum; Yohana Widya Oktaviani (Universitas Pendidikan Nasional, 2022)
The purpose of this study is to determine the form of additional sanctions that can be applied to corporations in various provisions of the applicable laws and regulations and to analyse the application of various provisions related to additional forms of criminal sanctions as environmental restoration in court decisions. The research method used is normative juridical, namely legal research using library research, by conducting research through library materials or secondary and tertiary data. The form of additional sanctions that can be imposed on companies/corporations in environmental crimes under different statutory provisions. Then the application of additional criminal sanctions oriented towards environmental recovery in court decisions is still rarely implemented properly. Of the two court decisions, only one has complied with applicable regulations and is oriented towards environmental sustainability. The benefits of this research are as a reference source for government agencies to solve problems and environmental management, and can be used as a guide in the search for truth and legal certainty and can be used as a reference in future research.